Diversity and function of soluble heterodisulfide reductases in methane-metabolizing archaea - Xingyu Lyu; Hang Yu; Yahai Lu (Microbiology Spectrum)
ABSTRACT Soluble heterodisulfide reductase subunit A (HdrA) is an ancient protein central to energy metabolism, facilitating the recycling of intermediates in methane metabolism and performing flavin-based electron bifurcation for energy conservation. In this study, we investigated the functional diversity and evolutionary dynamics of HdrA in methane-metabolizing archaea. An analysis of 1,152 HdrA sequences from 624 genomes revealed that HdrA diversified through internal domain modifications, resulting in 28 distinct classes and 4 major types (types I, Ia, II, and III). Functional genes in HdrA gene clusters revealed variations in mid-potential electron donors, including NADH, F420H2, H2, and formate. Two major types of HdrA have not previously been studied in detail. Type II HdrA resulted from a fusion of two different classes of type I HdrA. Particularly, a consistent gene cluster containing type II HdrA, molybdopterin oxidoreductase, and F420 dehydrogenase was identified in anaerobic methane-oxidizing archaea and methanogens. Protein sequence and structural predictions suggested that the molybdopterin oxidoreductase protein had lost its catalytic function, and F420H2 served as the mid-potential electron donor or acceptor for the Hdr protein complex. This gene cluster may expand to include additional type I HdrA and HdrD, potentially supporting two electron bifurcation events to lower electron potential for ferredoxin reduction. Type III HdrA, with an inserted GltD domain compared to type I HdrA, appears to have altered the electron transfer route and may use NADH as its mid-potential electron donor or acceptor. The remarkable functional flexibility of HdrA likely helps methane-metabolizing archaea adapt to diverse anaerobic environments.IMPORTANCEAll methanogenic archaea use heterodisulfide of coenzymes M and B as the terminal electron acceptor. In anaerobic methane- and alkane-oxidizing archaea, the reverse reaction occurs. The cycling of heterodisulfide is vital to the energy conservation of these anaerobic microorganisms. Soluble heterodisulfide reductase is an ancient protein fulfilling this function via flavin-based electron bifurcation or confurcation. Despite being present in the vast majority of methane- and alkane-metabolizing archaea, the diversity and evolution of this key protein have not been investigated. This study reveals substantial domain variation and structural changes in the key bifurcating subunit HdrA in methane- and alkane-metabolizing archaea. The resulting flexibility of HdrA enables the protein complex to vary its interacting subunits and electron carriers based on the organisms’ primary metabolism. Our findings shed light on how methane- and alkane-metabolizing archaea thrive in various anaerobic environments, contributing to our broader understanding of carbon cycling and energy conservation.